PENDAMPINGAN PENGGUNAAN MEDIA SOSIAL DALAM PEMASARAN PRODUK UMKM DESA SAKO - Febriana Feby; Salsabila nirisna; Anindya yona; Sandy kurniawan; Aryanti; Fernando Africano (Universitas Sumatera Barat, 2025)
This community service program aimed to enhance the capabilities of Micro, Small, and Medium Enterprises (MSMEs) in Sako Village, Rambutan District, Banyuasin Regency, South Sumatra Province, in utilizing social media as a product marketing tool. The program was initiated due to the low level of digital literacy and the limited marketing strategies used by MSME actors in the area. The activities were conducted using a qualitative method with a descriptive approach, including discussions, seminars, lectures, and hands-on practice. Data were collected through observation, interviews, and documentation, then analyzed descriptively to assess the impact of the mentoring activities. The results showed a significant improvement in the participants' understanding and skills in using social media platforms such as Instagram and Facebook to promote their products. Training participants became more capable of creating structured marketing content, using interactive features, and even utilizing paid advertisements to expand market reach. The conclusion is that direct and interactive training-based mentoring can effectively foster digital transformation among MSMEs, making them better prepared to face modern market challenges and improve their business competitiveness.